Nontechnological Online Challenges Faced by Health Professions Students during COVID-19: A Questionnaire Study - Abdulmalik Khalid Alshamsi; Ken Masters (MDPI AG, 2022)
COVID-19 forced universities to shift to online learning (emergency remote teaching (ERT)). This study aimed at identifying the nontechnological challenges that faced Sultan Qaboos University medical and biomedical sciences students during the pandemic. This was a survey-based, cross-sectional study aimed at identifying nontechnological challenges using Likert scale, multiple-choice, and open-ended questions. Students participated voluntarily and gave their consent; anonymity was maintained and all data were encrypted. The response rate was 17.95% (n = 131) with no statistically significant difference based on gender or majors (p-value > 0.05). Of the sample, 102 (77.9%) were stressed by exam location uncertainty, 96 (73.3%) felt easily distracted, 98 (74.8%) suffered physical health issues, and 89 (67.9%) struggled with time management. The main barriers were lack of motivation (92 (70.2%)), instruction/information overload (78 (59.5%)), and poor communication with teachers (74 (56.5%)). Furthermore, 57 (43.5%) said their prayer time was affected, and 65 (49.6%) had difficulties studying during Ramadan. The most important qualitative findings were poor communication and lack of motivation, which were reflected in student comments. While ERT had positive aspects, it precipitated many nontechnological challenges that highlight the inapplicability of ERT as a method of online learning for long-term e-learning initiatives. Challenges must be considered by the faculty to provide the best learning experience for students in the future.